Venetian expertise at the service of the king. Science and power struggles in 16th-Century Seville - Mardegan, Riccardo (Cuadernos de Historia Moderna, 2026)
This article analyzes a legal conflict in 16th-century Seville surrounding the monopoly of the ship careening trade, granted to Andrea Barrasi and Pablo Matía. Through the lawsuit with fellow careener Juan Guillermo, the tensions between technical knowledge, justice, and economic power in the context of Atlantic trade are revealed. The study highlights the involvement of sailors, laborers, and technicians in jurisdictional disputes, as well as the active presence of Venetians in the port of Seville. The circulation of knowledge and technologies between the Mediterranean and the Atlantic shows how technical margins were fundamental in shaping the Empire. The microhistorical approach sheds light on global processes from a local perspective.
Keywords: microhistory; Atlantic trade; lawsuit; technical knowledge; Venetians